The association of hand and wrist injuries with other injuries in multiple trauma patients. A retrospective study in a UK Major Trauma Centre. Issue 7 (July 2021) - Tsinaslanidis, P.; Smith, Toby O.; Brown, O.S.; Tsinaslanidis, G.; Umarji, S.; Hing, CB
Highlights: The incidence of hand and wrist injuries in multiply injured trauma patients in our series was 26.2%. A significant association was found between a hand or wrist injury and a lower limb or pelvic injury. Clinical recommendations are made to emphasise careful screening of hand and wrist injuries in this population. Abstract: Background: Approximately 20, 000 major trauma cases occur in England every year. However, the association with concomitant upper limb injuries is unknown. This study aims to determine the incidence, injury pattern and association of hand and wrist injuries with other body injuries and the Injury Severity Score (ISS) in multiply injured trauma patients. Methods: Single centre retrospective study was performed at a level-one UK Major Trauma Centre (MTC). Trauma Audit and Research Network (TARN) eligible multiply injured trauma patients that were admitted to the hospital between January 2014 and December 2018 were analysed. TARN is the national trauma registry. Eligible patients were: a trauma patient of any age who was admitted for 72 h or more, or was admitted to intensive care, or died at the hospital, was transferred into the hospital for specialist care, was transferred to another hospital for specialist care or for an intensive care bed and whose isolated injuries met a set of criteria. Data extracted included: age, gender, mode of arrival, location of injuries including: hand and/or wrist and mechanism of injury. We performed a logistic regression analysis to assess the association between hand/wrist injury to ISS score of 15 points or above/below and to the presentation of other injuries. Results: 107 patients were analysed. Hand and wrist injuries were the second most common injury (26.2%), after thoracic injuries. Distal radial injuries were found in 5.6%, carpal/carpometacarpal in 6.5%, concurrent distal radius and carpometacarpal in 0.9%, phalangeal injuries in 4.7%, tendon injuries in 0.9% and concurrent hand and wrist injuries in 7.5% cases. There was a significant association between hand or wrist injuries and lower limb injuries (Odds Ratio (OR): 3.84; 95% confidence intervals (CI): 1.09 to 13.50; p = 0.04) and pelvic injuries (OR: 4.78; 95% CI: 1.31 to 17.44; p = 0.02). There was no statistical association between hand and wrist injuries and ISS score (OR: 0.80; 95% CI: 0.11 to 5.79; p = 0.82). Conclusions: Hand and wrist injuries are prevalent in trauma patients admitted to MTCs. They should not be under-estimated but routinely screened for in multiply injured patients particularly those with a pelvic or lower limb injury.